Pengaruh Kecepatan Mata Pisau dan Jumlah Bahan Terhadap Waktu Produksi Cabai Bubuk Pada Mesin Disc Mill FFC15 - M. Caesar Miftakhul Falah; Ach. Muhib Zainuri (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
One of the most profitable horticultural crops, but it spoils quickly due to its high water content. Processing chili peppers with a disc mill into chili powder is a great way to increase the added value of the product while extending its shelf life. The purpose of this study was to determine how the blade rotation speed and amount of material affected the production time of chili powder in an FFC15 Disc Mill. The blade rotation speed varied between 2100 rpm and 3500 rpm, and the amount of material varied between 5% and 500 g. The data were analyzed using statistical analysis to determine the effect of each component and their relationship with each other. The results showed that the blade rotation speed and the amount of material had a significant effect on the production time of chili powder. However, the relationship between these two factors did not have a significant effect. The best operating conditions were achieved with 500 grams of material and a speed of 3500 rpm, which resulted in the fastest production time of 4.367 minutes.